The influence of gender and group membership on food safety: The case of meat sellers in Bodija market, Ibadan, Nigeria - Grace, Delia; Olawoye, J.; Dipeolu, M.; Odebode, S.; Randolph, Thomas F. (Springer, 2012)
We describe a study to assess the bacteriological quality and safety of meat in Bodija market in Ibadan and to investigate the influence of gender and group membership on food safety. Mixed methods were used to gather information on meat safety and related socioeconomic factors. These methods included a participatory urban appraisal, focus group discussions with eight butchers’ associations, in depth discussions with six key informants, a questionnaire study of 269 meat sellers and a cross-sectional survey of meat quality (200 samples from ten associations). We found that slaughter, processing and sale of beef meat take place under unhygienic conditions. The activities involve both men and women, with some task differentiation by gender. Meat sold by association members is of unacceptable quality. However, some groups have consistently better quality meat and this is positively correlated with the proportion of women members. Women also have significantly better food safety practice than men, though there was no significant difference in their knowledge of and attitude towards food safety. Most meat sellers (85 %) reported being ill in the last 2 weeks and 47 % reported experiencing gastrointestinal illness. Eating beef, eating chicken, eating offal, consuming one’s own products and belonging to a group with poor quality of meat were all strong and significant predictors of self-reported gastrointestinal illness. We include that gender and group membership influence meat quality and self-reported gastrointestinal illness and that butchers’ associations are promising entry points for interventions to improve food safety.